Accelerating a green recovery of cities: Lessons from a scoping review and a proposal for mission-oriented recovery towards post-pandemic urban resilience. (July 2021) - Moglia, Magnus; Frantzeskaki, Niki; Newton, Peter; Pineda-Pinto, Melissa; Witheridge, Jennifer; Cook, Stephen; Glackin, Stephen
Abstract: In the post-pandemic era, we must value our cities as cultural and economic centres, that are socially and environmentally diverse. This requires a transformation in the way we plan and govern our cities, but what can be learnt from the current crisis about how cities should be managed? In this article, we report on a scoping review to help identify seven lessons learnt for cities from the COVID-19 pandemic. We build on these lessons through a synthesis, outlining three urban missions that will chart a green urban recovery. The missions are to accelerate the urban mobility transition; to attain regenerative urban development; and create resilient urban infrastructure. We expand on what these missions entail, by defining six pathways that supports transition of urban mobility, energy, food, housing, health and nature. These pathways, when implemented in an integrated manner, provides a roadmap for green recovery in cities, that also builds resilience. Highlights: We report on a scoping review of urban issues highlighted by COVID-19. A green recovery in cities based on our three missions supports urban resilience. Mission 1: Accelerate the urban mobility transition to minimise private car use. Mission 2: Develop and adopt regenerative urban design for people and nature. Mission 3: Invent and invest in urban resilient infrastructures for future generations.